2012
DOI: 10.1016/j.cell.2012.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Piwi-Interacting RNAs Protect DNA against Loss during Oxytricha Genome Rearrangement

Abstract: Summary Genome duality in ciliated protozoa offers a unique system to showcase their epigenome as a model of inheritance. In Oxytricha, the somatic genome is responsible for vegetative growth, while the germline contributes DNA to the next sexual generation. Somatic nuclear development removes all transposons and other so-called “junk DNA”, which comprise ~95% of the germline. We demonstrate that Piwi-interacting small RNAs (piRNAs) from the maternal nucleus can specify genomic regions for retention in this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
232
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(238 citation statements)
references
References 75 publications
5
232
0
1
Order By: Relevance
“…The shift in expression of the two paralogs may have either provided an opportunity for Rpb2-a to acquire Pol-II-independent functions in early zygotes or been a consequence of that specialization. Fang et al (2012) identified the presence of Rpb2-a in the Otiwi-1 complex by co-immunoprecipitation with a specific Piwi antibody (Fang et al 2012). Otiwi-1 is expressed in the parental macronuclei at 12 hr and then localizes to the zygotic macronucleus and micronucleus at 18 hr, a pattern similar to that of Rpb2 ( Figure S6).…”
Section: Rpb2-a Is Absent From the Pol-ii Complex In Early Zygotesmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift in expression of the two paralogs may have either provided an opportunity for Rpb2-a to acquire Pol-II-independent functions in early zygotes or been a consequence of that specialization. Fang et al (2012) identified the presence of Rpb2-a in the Otiwi-1 complex by co-immunoprecipitation with a specific Piwi antibody (Fang et al 2012). Otiwi-1 is expressed in the parental macronuclei at 12 hr and then localizes to the zygotic macronucleus and micronucleus at 18 hr, a pattern similar to that of Rpb2 ( Figure S6).…”
Section: Rpb2-a Is Absent From the Pol-ii Complex In Early Zygotesmentioning
confidence: 99%
“…Cells were maintained in Pringsheim buffer [0.11 mM Na 2 HPO 4 , 0.08 mM MgSO 4 , 0.85 mM Ca(NO 3 ) 2 , 0.35 mM KCl, pH 7.0] with Chlamydomonas reinhardtii and Klebsiella as the food source, as in Fang et al 2012. To initiate conjugation, cells were starved and mixed in equal numbers after food depletion.…”
Section: Cell Culturementioning
confidence: 99%
“…Interestingly, piRNAs direct specific genome rearrangements in ciliates and this precise genome editing results in either somatic elimination [72] or retention [73] , indicating the versatility of this particular RNAi pathway. PiRNAs can target mRNAs through a PTGS-like mechanism, however they may also induce TGS by directing heterochromatin formation at the target regions [74,75] .…”
Section: Pirnasmentioning
confidence: 99%
“…During the development of the somatic nucleus, Oxytricha gets rid of all parasitic DNA elements, which compose the majority of the germline DNA (>95%). It was known that RNA guides DNA rearrangements in Oxytricha [65], however only recently it was shown that piRNAs are central to this process [66]. piRNAs that match genes present in the somatic genome are transgenerationally inherited from the maternal nucleus.…”
Section: Guest List: Rna Licensingmentioning
confidence: 99%
“…This model w as validated when synthesized piRNAs that match regions that are otherwise deleted were injected into Oxytricha cells. It was shown that these artificiallyproduced piRNAs instruct the germline to refrain from deleting the corresponding DNA sequences, so that these DNA regions are kept in later generations [66]. Thus, if RNAimediated immunity is normally thought of as a strategy to dispose of "foreign" sequences, the Oxytricha's RNAi system does the opposite -it protects its genome by discarding its entire somatic DNA, and licensing the inclusion of self-genes only.…”
Section: Guest List: Rna Licensingmentioning
confidence: 99%